Methods of State Regulation of the Spheres of Natural Monopolies - Maftuna, Samieva (ANTIS PUBLISHER, 2024)
This scientific article covers the methods of state regulation and management of the spheres of natural monopolies. The reasons for the origin of natural monopolies in the market, their negative consequences in the economy are covered. Proposals and recommendations have been developed on the economic features of the regulation of natural monopolies.